CHILD RIGHTS BY DESIGN: UNBOXING CHILDREN FROM THE CHILD-ONLY DIGITAL CORNER - Pothong, Kruakae; Livingstone, Sonia (AoIR Selected Papers of Internet Research, 2023)
Digital technologies now mediate most, if not all, aspects of children’s lives from learning to lunching, playing, staying connected and building relationships with friends and family. However, the same cannot be said about children’s best interests in the design and operation of today’s digital environment. This paper analyses 52 products and services children use, including consoles, mobile games, wearables, smart toys, EdTech and digital health services, for their features and stated compliance with existing standards and regulations. The analysis reveals that each of these products states compliance with just 5.5 standards and regulations on average. This paper then contributes a framework for digital providers to design children’s rights into their products and services, based on interviews with experts, ranging from designers to lawyers and human rights experts, and workshops with designers from large to start-up companies. It argues that if a digital world is made child-rights-respecting by design, children can explore and reap full benefits of what digital technologies can offer alongside their older counterparts.